2009
DOI: 10.1109/tpds.2008.148
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Network Quality on Player Departure Behavior in Online Games

Abstract: Abstract-Understanding the impact of network conditions on player satisfaction, which is one of the major concerns of network game designers, is a popular research topic. Of the various ways to gauge user satisfaction, in this paper, we focus on how network quality affects a player's decision to leave a game prematurely. To answer this question, we analyze a 1, 356-million-packet trace from a large commercial MMORPG called ShenZhou Online.We show that both network delay and network loss significantly affect a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 35 publications
(48 reference statements)
0
23
0
Order By: Relevance
“…it rate, noted λ(t), is the probability that a player stops playing and never plays again a erwards, in a small interval of time, knowing that he was playing just before. Among many authors, it was used by Chen et al to model the impact of network quality on player departure [4].…”
Section: Survival Analysis 31 Retentionmentioning
confidence: 99%
“…it rate, noted λ(t), is the probability that a player stops playing and never plays again a erwards, in a small interval of time, knowing that he was playing just before. Among many authors, it was used by Chen et al to model the impact of network quality on player departure [4].…”
Section: Survival Analysis 31 Retentionmentioning
confidence: 99%
“…Survival analysis has already been used in video game analysis. Chen [5] use survival analysis to quantify the effect of network quality on player retention in Online Games. They found that both network delay and network loss have a link with player retention.…”
Section: Related Workmentioning
confidence: 99%
“…In RPUS, first, Si sends out all the relaying requests of the local avatars to other servers and receives the relaying requests from other servers (lines 1-3). Then, Si tries to relay the update packets to the replicas for all the relaying requests received from other servers (lines [4][5][6][7][8][9][10][11][12]. After that, Si updates the replicas without QoS of the local avatars maintained by the clients connected to itself according to the available resources (lines 13-17).…”
Section: Update Strategy Descriptionmentioning
confidence: 99%
“…The problem of providing QoS in a DVE system has been already described in many ways. Firstly, some research work has been done on the influences of network quality on consistency and player departure behavior in DVEs [7,14]. It shows the consistency plays an important role in the players' behaviors.…”
Section: Introductionmentioning
confidence: 99%